Visceral Metastasis: A Prognostic Factor of Survival in Patients with Spinal Metastases - Lun, Deng‐xing; Chen, Nai‐Wang; Feng, Jiang‐tao; Yang, Xion‐gang; Xu, Zhao‐wan; Li, Feng; Hu, Yong‐cheng (Orthopaedic surgery, 2020)
Objective To characterize the visceral metastasis as a predictive tool for the survival of patients with spinal metastases through an exploratory meta‐analysis. Methods Two investigators independently searched PubMed and Embase databases for eligible studies from 2000–2016. The effect estimates for the hazard ratio (HR) or risk ratio (RR) and 95% confidence interval (CI) were collected and pooled with a random‐ or fixed‐effect model. Results In total, 18 eligible studies were retrieved with 5468 participants from nine countries. The overall pooled effect size for HR and RR was 1.50 and 3.79, respectively, which was proved to be statistically significant. In the subgroup of prostate cancer (PCa) and non‐small cell lung cancer (NSCLC), statistical significance and marginal statistical significance was presented for the pooled HR (HR = 1.76, 95% CI 1.35–2.29) and (RR = 1.56, 95% CI 0.99–2.48), respectively. However, in the subgroup of thyroid cancer, breast cancer, and renal cancer, statistical significance was not achieved (HR = 1.17, 95% CI 0.75–1.83, Z = 0.70, P = 0.486). The results did not show any evidence of publication bias. Conclusions This study demonstrated that visceral metastasis was a significant prognostic factor in patients with spinal metastases as a whole. Interestingly, the onset of visceral metastases differentially impacted the survival in different primary tumors. Therefore, the prognostic value of visceral metastasis might be related to the type of primary tumor.